Description of Parental Characteristics on the Level of Anxiety of Parents Whose Children Are Being Treated in the P ICU at Dr Wahidin Sudirohusodo Hospital Makassar - Nur Aisyah (PT Inovasi Pratama Internasional, 2023)
Based on the research results Helena (2008) concluded from the 11 respondents who had a good knowledge gained 7 respondents experienced mild anxiety (63.6%), 3 respondents had moderate anxiety (27.2%) and 1 respondent suffered from severe anxiety (9.1%). The purpose of this study is to know the description of characteristics of parents towards anxiety level of parents whose children were hospitalized in PICU. This was descriptive research. This study will describe the association between parents; characteristics and anxiety level. The results showed that of the 40 samples studied based on the characteristics of sex, male sex as many as 7 people (17.5%) and female sex as many as 33 people (82.5%), the characteristics of age, it was shown younger age group as many as 14 people (35.0%) and older age group as many as 26 people (65%), obtained with low education as many as 10 people (25.0%) and high education as many as 30 people (75%), all respondents work (100%) or 40 respondents. The level of parental anxiety, experiencing mild anxiety level as many as 16 people (40%), anxiety levels were as many as 14 people (35%) and severe anxiety level as many as 10 people (25%). Expected in the implementation of nursing and medical measures should still pay attention to the principle of the provision of information and education of patients about the actions to be taken in order to better understand thus enhancing individual coping and reducing parental anxiety.